The Wiley Handbook of Violence and Aggression 2017
DOI: 10.1002/9781119057574.whbva088
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Recidivism and Violent and Aggressive Offenders

Abstract: Interventions that are effective in reducing recidivism and enhancing desistance are growing, but research into whether they work and how they work is rare. In keeping with the risk principle of the risk‐need‐responsivity model, risk‐reducing interventions have the most impact on the highest‐risk offenders. Developmental theory and longitudinal cohort research indicate that those who commit the most violent acts are also prolific and diverse offenders who start offending early, persist well into adulthood, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
1
0
0
Order By: Relevance
“…High levels of PCL-psychopathy are a feature of high-risk prisoner samples, a finding that is to be expected given that the PCL-R is widely used to predict criminal risk (Douglas et al, 2018). Our results are also consistent with research with an earlier sample of high risk New Zealand male prisoners, which found that on average they also obtained high scores on the PCL-SV ( M = 19.8, SD = 3.1, mdn = 20.0; Polaschek, 2008). But in contrast to the PCL scales, where scores are more directly based on criminal behavior and criminal lifestyle correlates, only the Disinhibition scale of the TriPM correlated with recidivism; it also continued to predict it directly in the multivariate models.…”
Section: Discussionsupporting
confidence: 92%
“…High levels of PCL-psychopathy are a feature of high-risk prisoner samples, a finding that is to be expected given that the PCL-R is widely used to predict criminal risk (Douglas et al, 2018). Our results are also consistent with research with an earlier sample of high risk New Zealand male prisoners, which found that on average they also obtained high scores on the PCL-SV ( M = 19.8, SD = 3.1, mdn = 20.0; Polaschek, 2008). But in contrast to the PCL scales, where scores are more directly based on criminal behavior and criminal lifestyle correlates, only the Disinhibition scale of the TriPM correlated with recidivism; it also continued to predict it directly in the multivariate models.…”
Section: Discussionsupporting
confidence: 92%